Fertilidad y fecundidad en Poeciliopsis turrubarensis (Pisces: Poeciliidae) - Cabrera Peña, Jorge (Universidad de Costa Rica, 1995)
Reproduetive analysis of 428 females of Poeciliopsis turrubarensis eollected in estuary of Panamá river, Culebra Bay, Guanacaste, Costa Rica, Was made. Por each female included in the random sample standard length, total length and weight were measured. Eaeh female was dissected and the brood was extracted and analized. Ovules, eggs and embryos were separated in to categories. Analysis of data detennined tha! this species has superfetation and they are sexually active al! year. The mean fertility was 31.43±16.94 (eggs + embryonic stage) and the fecundity was 18.5±lO.93 ovules. The minimun reproductive size, was 35.00 mm SL.